The role of a green economy in revitalising shrinking cities: Comparative case studies in France and Mexico - di Pietro, Simone (Quaestiones Geographicae, 2023)
This paper aims to research different strategies for developing the green economy in shrinking cities. Considering urban shrinkage and the green economy as two extended concepts, a French town in post-Fordist transition and a Mexican post-mining town are selected as the most diverse/similar systems to indicate different strategies for sustainable development in shrinking cities. Embedded into different national backgrounds, including urban dynamics and support schemes for the green economy, the selected cases share the objectives of greening and regrowing strategies relying on other sectors of the green economy. The methodology applied is qualitative, including fieldwork, semi-structured interview techniques, carried out in person or remotely, and questionnaires. Findings show some positive results regarding sustainability and ecological transition in the French case, while regrowth trends were reached in the Mexican case. However, the analysis leads to uncertain scenarios for positive long-term impacts, especially due to uncertainty around future supporting policies for territorial cohesion and sustainability at national and regional levels.